1988
DOI: 10.1175/1520-0469(1988)045<1678:eiohi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Hurricane Intensification

Abstract: Though qualitatively similar in structure. different hurricanes can attain different peak intensities during their lifetimes. Forecasters and empiricists relate the intensity to the sea surface temperature and the "effectiveness" of the upper troPospheric outflow. but offer no clear explanation of how the latter operates. Numerical modelers usually ignore the surrounding flow and emphasize interaction between the convective and vortex scales exclusively. This paper examines more closely the observed upper-trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(155 citation statements)
references
References 66 publications
8
147
0
Order By: Relevance
“…Indeed, the primary determinant of intensity change appears to be the relationship of the storm to the upper-tropospheric flow features, particularly those that constrain storm outflow and enhance vertical wind shear, in agreement with many previous studies (e.g., Rodgers and Gentry 1983;Holland and Merrill 1984;Merrill 1988;Molinari and Vollaro 1989;Rodgers et al 1991;Hanley et al 2001;Kimball and Evans 2002;Rappin et al 2010). FIG.…”
Section: A Composite View Of the Sal And Hurricanessupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, the primary determinant of intensity change appears to be the relationship of the storm to the upper-tropospheric flow features, particularly those that constrain storm outflow and enhance vertical wind shear, in agreement with many previous studies (e.g., Rodgers and Gentry 1983;Holland and Merrill 1984;Merrill 1988;Molinari and Vollaro 1989;Rodgers et al 1991;Hanley et al 2001;Kimball and Evans 2002;Rappin et al 2010). FIG.…”
Section: A Composite View Of the Sal And Hurricanessupporting
confidence: 88%
“…They suggested that the SAL negatively impacts tropical cyclones in the following ways: 1) the enhanced low-level temperature inversion, maintained by radiative warming of dust, suppresses deep convective development; 2) vertical wind shear caused by an increase in the lowlevel easterlies associated with the AEJ inhibits tropical cyclone intensification, based upon studies that have shown that shear tends to weaken storms (Gray 1968;Merrill 1988;DeMaria andKaplan 1994, 1999;Frank and Ritchie 2001;Rogers et al 2003;Braun and Wu 2007); and 3) intrusions of dry SAL air into tropical cyclones foster enhanced cold downdrafts (Emanuel 1989;Powell 1990) and lower the convective available potential energy within tropical cyclones. While it was not Dunion and Velden's intention to imply that the SAL's impacts were always negative or were the dominant factor affecting hurricane activity (J.…”
Section: Introductionmentioning
confidence: 99%
“…3. This figure shows that for a given SST in the indicated SST range the minimum surface pressure revealed as the maximum intensity curve for western North Pacific storms is lower than the potential minimum surface pressures for North Atlantic storms analyzed by Merrill (1987Merrill ( , 1988 and DK. This is also true for the 99th intensity percentile curve except for the slightly lower minimum surface pressure in Merrill's curve in the 29C SST group.…”
Section: Data and Analysis Methodsmentioning
confidence: 74%
“…For the western North Pacific, Baik and Paek (1998) advanced a proportion of 37%. This clearly signifies that factors such as a strong vertical wind shear between the lower and the upper troposphere, the intrusion of dry air or the weakness of the divergence in the upper troposphere have a considerable influence in limiting the intensification of cyclones (Merril, 1988). In the northern Indian Ocean, if one simply considers cyclones having reached a minimum of 65 knots, only 5.66% (3 of 53) approached or attained their maximum potential intensity over the last three decades.…”
Section: Intense Cyclones Considerably Influenced By Nearby Land Massesmentioning
confidence: 99%